Using the trajectory of the shuttlecock as a measure of performance accuracy in the badminton short serve - Vial, S.; Cochrane, J.; Blazevich, A. J.; Croft, J. L. (International Journal of Sports Science & Coaching, 2019)
Accuracy of a projectile is typically quantified as the proportion of successful target hits, or the distance an object finishes from the target. Serving in sports such as badminton differs since the shuttlecock is usually intercepted by the opponent before landing on the target (i.e. court surface). Therefore, landing accuracy measures are inappropriate and a new method of determining accuracy of the serve is needed. During interviews, elite coaches and players described an accurate short serve as crossing the net with low clearance and having an apex before the net. Three-dimensional trajectory of the shuttlecock was therefore tracked from eight national-level players who performed 30 short serves in simulated match conditions (i.e. with an opponent); 27% of all serves were classified as `accurate`, 27% of serves as `inaccurate`, 21% with a `good apex` position, and 25% with a `good clearance` height. The proposed method of assessing shuttlecock trajectory as a measure of accuracy could be adopted by coaches and players to assess and improve short serve accuracy. Furthermore, this method is more representative of a match environment since the shuttlecock rarely lands because the opponent returns the serve.